2021
DOI: 10.1038/s41467-021-22286-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activation of pH-responsive oxidase-like graphitic nanozymes for selective killing of Helicobacter pylori

Abstract: Helicobacter pylori infection is a major etiological factor in gastric diseases. However, clinical antibiotic therapy for H. pylori is limited by continuously decreased therapeutic efficacy and side effects to symbiotic bacteria. Herein, we develop an in vivo activatable pH-responsive graphitic nanozyme, PtCo@Graphene (PtCo@G), for selective treatment of H. pylori. Such nanozymes can resist gastric acid corrosion, exhibit oxidase-like activity to stably generate reactive oxygen species only in acidic gastric m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 47 publications
0
110
0
Order By: Relevance
“…After three-week infection, the results of urease test, plate coating and hematoxylin-eosin (H&E) staining showed that the H. pylori infected mice were successfully modeled (Figure S18, Supporting Information). [20] Next, the corresponding intragastric administration was carried out, and the mice were sacrificed on the second day after stopping administration for subsequent biochemical experiments. The antibacterial capacity of Pd(H) @ ZIF-8 @ AP in vivo was initially evaluated.…”
Section: In Vivo H Pylori Infection Therapy Of Pd(h) @ Zif-8 @ Apmentioning
confidence: 99%
“…After three-week infection, the results of urease test, plate coating and hematoxylin-eosin (H&E) staining showed that the H. pylori infected mice were successfully modeled (Figure S18, Supporting Information). [20] Next, the corresponding intragastric administration was carried out, and the mice were sacrificed on the second day after stopping administration for subsequent biochemical experiments. The antibacterial capacity of Pd(H) @ ZIF-8 @ AP in vivo was initially evaluated.…”
Section: In Vivo H Pylori Infection Therapy Of Pd(h) @ Zif-8 @ Apmentioning
confidence: 99%
“…As presented in Supplementary Fig. 24 , we have analyzed the intrinsic oxidase-mimetic activity of these Art Ms, which suggests that the Fe-Art M exhibits very high catalytic transformation of oxygen into ROS via activation and cleavage of the O–O bond 33 . This good contact killing activity of Fe-Art M preliminarily supports the proposed concept for the bacterial “capture and killing” function of hedgehog artificial macrophage.…”
Section: Resultsmentioning
confidence: 99%
“…They have been applied to energy science, electronics, flexible materials, catalytic science, imaging, environmental science, analytical sensing, and biomedicine. [151][152][153][154] As a new class of nanozymes, carbon has been extensively reported in this field. [155] For the graphene nanozymes, the GO-COOH nanozyme have been reported by Qu et al The fabricated GO-COOH nanozyme possess the horseradish PODlike enzymes catalytic.…”
Section: Non-metal-based Nanozymesmentioning
confidence: 99%